KOMUNIKASI POLITIK POLITISI PEREMPUAN INDONESIA RAYA (PIRA) JAWA BARAT DALAM MENDUKUNG UU TPKS - Harahap, Silfina Rahmi; Suhaeri (KOMUNIKA BANGSA, 2025)
Political Communication of Indonesian Women Politicians Greater Indonesia (PIRA) West Java shows how support is given by women as politicians who are involved in a wing of a political party for policies agreed upon by their political parties. This research will explain the forms of support carried out by PIRA politicians and what are the challenges faced by PIRA in supporting the TPKS Law, then how political communication is carried out by West Java PIRA politicians in supporting the TPKS Law. By using a qualitative research method with a qualitative descriptive approach with the aim of seeing how the support is provided and what challenges are faced with the existence of this TPKS Law. Then how is the political communication carried out by PIRA as a female politician. The results of this study indicate that the support provided by PIRA is by socializing the benefits and importance of the TPKS Law on the internalization of PIRA beforehand to focus on the quality of each PIRA member. Then, in facing the challenges of the TPKS Law, PIRA found points including differences in views, discrimination against women politicians, lack of education in the community, and a budget that did not cover the needs of the TPKS Law itself. Therefore this study fully answers the objectives of the research conducted.